2022
DOI: 10.3389/fimmu.2022.974034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cuproptosis -related subtypes, the development of a prognosis model, and characterization of tumor microenvironment infiltration in prostate cancer

Abstract: Cuproptosis, Copper Induced Cell Death, is a newly defined type of programmed cell death, involving in the regulation of tricarboxylic acid (TCA) cycle. Dysfunction of cuproptosis induces cytotoxicity and influences the proliferation of multiple tumors. However, the direct prognostic effect of cuproptosis related genes and corresponding regulating mechanisms amid prostate cancer remains unknown. A multi-omics analysis strategy was adopted to explore the role of ten cuproptosis related genes in The Cancer Genom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…According to the current study, a novel signature based on the cuproptosis gene may be able to predict a patient's prognosis, biological makeup, and the best course of therapy for them if they have glioma or triple negative breast cancer [43,44]. The immune microenvironment and tumor immunotherapy may both be affected by cuproptosis-related lncRNAs at the same time [45][46][47].…”
Section: Discussionmentioning
confidence: 93%
“…According to the current study, a novel signature based on the cuproptosis gene may be able to predict a patient's prognosis, biological makeup, and the best course of therapy for them if they have glioma or triple negative breast cancer [43,44]. The immune microenvironment and tumor immunotherapy may both be affected by cuproptosis-related lncRNAs at the same time [45][46][47].…”
Section: Discussionmentioning
confidence: 93%
“…The functional role of cuproptosis in cancer development has been previously reported. For example, cuproptosis was used to predict clinical outcomes and immune response in bladder cancer [9], breast cancer [10], colorectal cancer [11], and prostate cancer [12]. A more recent study suggested that cuproptosis-related genes might be critically involved in the 2-year AML prognosis and the immune response to treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…12 Numerous cuproptosis-related genes, such as DLAT, showed considerable changes in DNA methylation and CNV, which had a significant impact on the prognosis of patients with PCa. 13 However, the role of cuproptosis in regulating Doce resistance remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, copper(II) bis (diethyldithiocarbamate)‐based nanoparticles demonstrated anti‐GSH cytotoxicity with an efficient reversal of the resistance to cisplatin, whereas GSH detoxified the lethal impact of cisplatin in A549 cells 12 . Numerous cuproptosis‐related genes, such as DLAT, showed considerable changes in DNA methylation and CNV, which had a significant impact on the prognosis of patients with PCa 13 . However, the role of cuproptosis in regulating Doce resistance remains unclear.…”
Section: Introductionmentioning
confidence: 99%